Esfera - BAENA RUIZ, Julián (SINTESIS, 1996)
Otros descriptores: POLIEDROS; EDUCACION SECUNDARIA; ENSEÑANZA SECUNDARIA.Colaboradores: CORIAT BENARROCH, Moisés; MARIN DEL MORAL, Antonio; MARTINEZ LOPEZ, Pedro S.